(untitled) (TEST Trento Student Law Review, 2023)
The rules governing the power of the International Criminal Court resort to a blurred concept such as that of "justice". Moreover, this problem is compounded by the fragile balance on which transitio- nal justice processes rest, particularly those in which it is accepted that the criminal sanction may be turned down in favor of the protection of higher interests. The outcome of this framework in a concrete case like the Colombian one could not have been any different than what it has been: almost twenty years of preliminary examination, a civil war that is not over yet, and much uncertainty. This article is an attempt to demon- strate how the combination of transitional and restorative justice is not only well possible but also compatible with the Rome Statute system. The norms of the ICC statute, both national and international case laws, and doctrinal interpretations all together show that if justice does not have a proper definition, it is thus able to acquire several different meanings, one of them being a system that does not pay tribute to the past but to the re- construction of the future. The validity of the theoretical reconstruction is strengthened by the Colombian case and its historical, political, and le- gal aspects. The quest for peace has been conducted through instruments like amnesties and reduced sanctions, showing that this is a possible path. The silence more than the words of the International Criminal Court contributed to this answer: transitional processes that do not have at their core a retributive vision, even excluding criminal sanctions, are compati- ble with the Rome Statute.